UHPFRC hidden capitals as an alternative method for increasing punching shear resistance of LWAC flat slabs. (15th November 2022) - Gołdyn, Michał; Urban, Tadeusz
Highlights: The effect of UHPFRC hidden capital placed in the compression zone of LWAC slab was investigated. Specimens with hidden capitals were characterized by deflections lower by about 16 ÷ 20% with respect to control specimen. Introduction of UHPFRC capitals allowed for increase in punching shear capacity of 29% or 82%, depending of fibre content. Failure mode (inside or outside the capital) was dependent on residual strength of UHPFRC, affected by fiber content. The load carrying capacities were evaluated in the light of Critical Shear Crack Theory including Variable Engagement Model. Abstract: Due to outstanding strength properties of contemporary ultra-high performance fiber reinforced concretes (UHPFRC), they can be successfully used to improve the punching shear resistance of flat slabs made from lightweight aggregate concrete (LWAC). However, the relatively high cost of UHPFRC means that the application is usually limited to the support zone or the subsurface layer of the slab. The paper presents the results of experimental investigations on application of the UHPFRC hidden capitals to increase punching shear capacity of LWAC slabs. The study was a continuation of the previous experimental program and included a total of three 200 mm thick slabs with the same longitudinal reinforcement ratio, equal to 1.23%. One was the control specimen made entirely from LWAC, while in the others 130 mm thick capitals from UHPFRC with 2.5% and 5.0% fiber content were cast. The application of hidden capitals allowed to increase the stiffness and reduce deflections of the slabs by about 16 ÷ 20%. The residual strength of UHPFRC was found to be the key feature. In case of the slab with capital from UHPFRC with 2.5% fibre content, shear crack formed at the edge of the column and crossed the capital. However, the contribution of UHPFRC strength allowed to increase the punching shear capacity by 29% with respect to the control specimen. The doubling of fiber content to 5.0% changed the failure mechanism, because the shear cracks formed at the edge of the capital, what was similar to observed in slabs failed outside punching shear reinforced area. This translated into a significant increase in the load capacity by 82% in comparison to the control slab. The performed analysis demonstrated the usefulness of the Critical Shear Crack Theory (CSCT) and the Variable Engagement Model (VEM) for the assessment of the punching shear resistance of LWAC slabs with hidden capitals from UHPFRC. A good agreement of load-rotation response and ratios of theoretical to experimental load equal to 0.87 and 1.16 were obtained. The calculations allowed for correct prediction of the failure mode – punching within or outside the capital.